2022
DOI: 10.3389/fmicb.2021.817615
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress Affects Faecal Microbial and Metabolic Alterations of Rabbits

Abstract: Heat stress can impair the rabbit immune system, induce oxidative stress, and cause many complications. These diseases are characterized by metabolic disorders, but the underlying mechanism is unknown. As a result, the current research determines the effects of HS on intestinal microorganisms in rabbits and the metabolic pathway disorders caused by HS. Twelve rabbits were randomly assigned to one of two groups: CON (22–24°C) and HS (30°C–32°C). Both the groups were treated for 15 days. Blood and fecal samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…An increase in the relative abundance of Devosia genus was found both in CKD-PD patients with VC when compared with CKD-PD patients without VC, as well as in CKD-PD patients with a higher mortality risk. To our knowledge, Devosia has not been reported previously in the blood microbiome but has been found to be increased in the gut microbiota of colorectal cancer patients [ 51 ] and in rabbits with heat stress [ 52 ], suggesting its possible translocation from the gut into the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the relative abundance of Devosia genus was found both in CKD-PD patients with VC when compared with CKD-PD patients without VC, as well as in CKD-PD patients with a higher mortality risk. To our knowledge, Devosia has not been reported previously in the blood microbiome but has been found to be increased in the gut microbiota of colorectal cancer patients [ 51 ] and in rabbits with heat stress [ 52 ], suggesting its possible translocation from the gut into the systemic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, they play an important role in the degradation of vegetable feed components and the production of SCFAs [ 2 ]. Regarding Akkermansia genus, it is part of the Verrucomicrobia phylum and it has been reported to positively regulate the production of antioxidant metabolites, protect the self-healing of the intestinal mucosal protective layer, and enhance the response to inflammatory reaction damage [ 6 ] The most well-known species in this genus is Akkermansia muciniphila , a mucin-degrading bacterium that has been demonstrated to be beneficial in rabbits as its ability to break down mucin is especially important during caecotrophy for optimal nutrient extraction [ 4 ]. Finally, the presence of Muribaculaceae family has not been reported previously in rabbit caeca but in mink gut it seems to be able to degrade complex carbohydrates [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, gut health has been defined as the absence, prevention or avoidance of intestinal disease so that the animal is able to perform its physiological functions in order to withstand exogenous and endogenous stressors [ 5 ]. To guarantee a healthy gut, an efficient mucosal barrier function through an adequate gut morphometry and morphology, a stable and diverse microbiota, and an effective intestinal immunity are needed to resist pathogen colonization and to ensure optimal digestion and absorption of nutrients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that HS can alter the gut microbiota of animals such as mice, rabbits, and chickens. [10][11][12] Dysbiosis of the gut microbiota, characterized by decreased concentrations of beneficial metabolites such as short-chain fatty acids and increased levels of pathogenic metabolites, 13 can trigger excessive activation of the immune system, 14 resulting in intestinal inflammation and discomfort. 15 Secretory immunoglobulin A (sIgA), the primary immunoglobulin in the intestinal mucosa, is produced primarily by B cells and serves as the first line of defense against various endogenous microbial communities and exogenous invasive pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…HSP70, as the most abundant member of the HSP family, has been shown to alter the composition of the gut microbiota and increase intestinal permeability, 9 leading to the infiltration and translocation of luminal antigens, endotoxins, and pathogenic bacteria. Studies have indicated that HS can alter the gut microbiota of animals such as mice, rabbits, and chickens 10–12 . Dysbiosis of the gut microbiota, characterized by decreased concentrations of beneficial metabolites such as short‐chain fatty acids and increased levels of pathogenic metabolites, 13 can trigger excessive activation of the immune system, 14 resulting in intestinal inflammation and discomfort 15 .…”
Section: Introductionmentioning
confidence: 99%